Carbon material-coated metal particle and method for producing the same
By employing a liquid phase method to coat metal particles with soluble carbon materials, the issues of poor flowability and high impurities in existing carbon-coating technologies are addressed, resulting in high-quality, highly fluid carbon-coated metal particles.
Patent Information
- Application Number
- JP2023163243
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-26
- Publication Date
- 2025-04-07
AI Technical Summary
Existing methods for carbon-coating metal particles face challenges such as poor flowability, high impurity levels, and non-uniform coating, particularly for fine powder structures.
The development of carbon-coated metal particles using a liquid phase method, where soluble carbon materials are contacted with metal particles in a solvent, allowing for uniform carbon coating and improved flowability.
The resulting carbon-coated metal particles exhibit high flowability, low impurity levels, and a high-quality carbon coating, enhancing their handling, transportability, and fillability in applications like powder metallurgy and 3D printing.
Smart Images

Figure 2025054062000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to high-quality carbon-coated metal particles having high fluidity and few impurities, and a method for producing the same. [Background technology]
[0002] Metals and alloys are used in a wide range of fields, and their powder forms, metal particles and alloy particles, are used in powder metallurgy, 3D printers, welding, and other applications.
[0003] Carbon coating by vapor phase film formation has been studied for the purpose of improving the corrosion resistance (e.g., acid resistance) and fluidity of the surface of, for example, plate-shaped metals that are not powders (Non-Patent Document 1). Also, carbon coating of metal particles by a solid phase method using a ball mill has been studied (Patent Documents 1 and 2). A method of carbon coating of metal particles by a vapor phase method using plasma CVD has been disclosed (Patent Document 3), and a method of carbon coating of metal particles by a liquid phase method using graphene or graphene oxide has been disclosed (Patent Document 4). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Patent No. 5387486 [Patent Document 2] JP 2021-085063 A [Patent Document 3] JP 2018-199862 A [Patent Document 4] JP 2018-184639 A [Non-patent literature]
[0005] [Non-Patent Document 1] Shinichi Miyano et al., Carbon, No. 247, p54-58 (2011) Summary of the Invention [Problem to be solved by the invention]
[0006] As mentioned above, metal particles are used in various applications, but they have a problem of poor fluidity. For example, in powder metallurgy, fluidity is important when filling a mold, and in 3D printer applications, fluidity is also important for filling a mold and transporting through a thin nozzle. Another problem is that carbon components remain and precipitate, and there are many impurities.
[0007] As mentioned above, carbon coating has been considered for stainless steel that is not in powder form, but it was difficult to coat the contacting parts of particles with the conventional gas-phase film-forming method for fine structures such as powder. Even when the powder is stirred, the agglomerates do not break down in the gas-phase method, making it difficult to uniformly coat each particle with carbon. In addition, carbon coating by solid-phase methods such as ball milling causes particle deformation in highly malleable particles such as metals and alloys, and the carbon components (e.g. carbon black) simply adhere to the particle surface, and the binding force is weak, making it difficult to coat uniformly because it is a solid-phase method. In addition, there was a problem that fine carbon components (e.g. carbon black particles) remain and become impurities. When carbon coating is performed on graphene or graphene oxide, which has a large size (in some cases more than several μm), it is difficult to uniformly cover the surface of the particles (wrinkles, overlaps, and gaps occur).
[0008] In view of the above circumstances, the present invention has an object to provide high-quality carbon-coated metal particles that are highly fluid and have few impurities, i.e., carbon-coated metal particles that are characterized by having a G-band peak by Raman spectroscopy and having a Kerr fluidity index of 70 or more, carbon-coated metal particles that are characterized by having a G-band peak by Raman spectroscopy and having a number ratio of particles consisting only of carbon of 1% or less when the particles are observed with an electron microscope or an optical microscope, and carbon-coated metal particles that are characterized by having a G-band peak by Raman spectroscopy and having a ratio of the total peak area derived from carbon-oxygen bonds (CO, C=O, etc.) to the total bond peak area of 10% or more when analyzed by O1sXPS, and a liquid phase production method thereof. [Means for solving the problem]
[0009] The present inventors have conducted various investigations to achieve the above object and have arrived at the present invention. That is, the present invention relates to carbon-coated metal particles having a G-band peak in a Raman spectrum obtained by Raman spectroscopy and a Kerr fluidity index of 70 or more, carbon-coated metal particles having a G-band peak in a Raman spectrum obtained by Raman spectroscopy and a particle number ratio of particles consisting only of carbon of 1% or less when observed with an electron microscope or an optical microscope, and carbon-coated metal particles having a G-band peak in a Raman spectrum obtained by Raman spectroscopy and a ratio of the total peak area derived from carbon-oxygen bonds (CO, C=O, etc.) to the total bond peak area of 10% or more when analyzed by O1sXPS, and a method for producing the carbon-coated metal particles is provided, the method being characterized by contacting a soluble carbon material with metal particles in a solvent. Effect of the Invention
[0010] By using the highly fluid stainless steel particles of the present invention and the method for producing the same, it is possible to provide stainless steel particles that have high fluidity and excellent handleability, transportability and packing properties. [Brief description of the drawings]
[0011] [Figure 1] FIG. 2 is a Raman spectrum diagram of particles of Example 1 of the present invention and Comparative Example 1. [Diagram 2] 1 is an optical microscope photograph of particles of Example 1 of the present invention and Comparative Example 1. [Diagram 3] 1 shows TG-DSC curves of particles of Example 1 and Comparative Example 1 of the present invention. [Figure 4] FIG. 2 is a Raman spectrum diagram of melt-solidified particles of Example 1 of the present invention and Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] The present invention will be described in detail below. Note that a combination of two or more of the individual preferred embodiments of the present invention described below is also a preferred embodiment of the present invention.
[0013] [Carbon-coated metal particles] The carbon-coated metal particles of the present invention have a G band (1580 cm due to the benzene hexagonal mesh structure) in Raman spectroscopy. -1 In addition, the D band (at 1350 cm due to defects and functional groups) -1 It is preferable that the carbon coating layer has a peak in the vicinity of the peak. By having these peaks, it can be characterized as having a skeleton as a carbon material, and it can be said to be a good carbon coating layer.
[0014] The carbon-coated metal particles of the present invention preferably have a Kerr fluidity index of 70 or more as determined by analysis using a Hosokawa Micron Powder Tester (PT-X). The Kerr fluidity index is the sum of the indices given to four items of analysis of the powder: angle of repose, spatula angle (average angle before and after impact), compressibility, and uniformity. More preferably, the Kerr fluidity index is 80 or more, and even more preferably, the Kerr fluidity index is 90 or more. A fluidity index of 70 or more is generally considered to be good, 80 or more is better, and 90 or more is the best. In other words, a metal particle having a Kerr fluidity index of 70 or more can be said to have good properties for handling as a powder.
[0015] The carbon-coated metal particles of the present invention preferably have an angle of repose of 40° or less, and more preferably 35° or less, which results in particles with high fluidity.
[0016] The carbon-coated metal particles of the present invention preferably have a spatula angle (before impact) of 50° or less, more preferably 40° or less, and preferably have a spatula angle (after impact) of 30° or less, more preferably 25° or less, which results in particles with high fluidity.
[0017] In the carbon-coated metal particles of the present invention, when the particles are observed under an electron microscope or an optical microscope, the number ratio of particles consisting of only carbon is preferably 1% or less. More preferably, it is 0.5% or less, and even more preferably, it is 0.1% or less. This results in high-quality carbon-coated metal particles. Note that, in the electron microscope, it is possible to distinguish between carbon-coated metal particles and particles consisting of only carbon by EDS mapping analysis. In the carbon-coated metal particles, metal components contained in the core particles are detected (for example, 50% or more), but in the particles consisting of only carbon, most of the components are carbon elements (for example, 50% or more). In the optical microscope, it is possible to distinguish whether the particles have a metallic luster or not. In the optical microscope, carbon-coated metal particles have a metallic luster, but particles consisting of only carbon are black. Note that, the particles consisting of only carbon refer to, for example, particles of 100 nm or more.
[0018] In the carbon-coated metal particles of the present invention, the ratio of the total peak area derived from carbon-oxygen bonds (CO bonds, C=O bonds, etc.) to the total bond peak area is preferably 10% or more when analyzed by O1sXPS. This results in high-quality carbon-coated metal particles having bonds between carbon, oxygen, and metal. The ratio is more preferably 15% or more, even more preferably 20% or more, particularly preferably 25% or more, and most preferably 30% or more.
[0019] The carbon-coated metal particles of the present invention preferably have a carbon content of 1% or less, more preferably 0.5% or less, and particularly preferably 0.3% or less. The carbon content is evaluated by the amount of weight loss when heated to a temperature equal to or higher than the carbon combustion temperature (e.g., 500°C).
[0020] The shape of the carbon-coated metal particles of the present invention is not particularly limited, but from the viewpoint of flowability, it is preferable that the particles be spherical or rounded, with the spherical shape being particularly preferable.
[0021] The carbon-coated metal particles of the present invention preferably contain particles having a particle size of 1 μm or more and 100 μm or less, as measured by observation with an optical microscope or a scanning electron microscope. By containing particles in this range, the particles have higher fluidity.
[0022] The carbon-coated metal particles of the present invention preferably have a volume average particle diameter D50 of 10 μm or more and 100 μm or less. When the volume average particle diameter D50 is in this range, the flowability is further improved.
[0023] It is preferable that the carbon-coated metal particles of the present invention have no peak in the G band in Raman spectroscopic analysis after sintering or heat melting and solidifying. This is because, as in the above, it is preferable that no carbon components remain after sintering or heat melting and solidifying (e.g., after welding). The carbon-coated metal particles of the present invention have a carbon coating layer to improve fluidity, but the carbon itself disappears when exposed to high temperatures such as heat melting. In other words, the carbon coating layer contributes to improving fluidity, but has no effect on the structure after heating (melting, sintering, etc.).
[0024] The carbon-coated metal particles of the present invention preferably have a Kerr fluidity index that is 5 or more higher than the raw metal particles or particles obtained by removing the carbon coating layer from the carbon-coated metal particles. In other words, the effect of the carbon coating layer preferably results in a Kerr fluidity index that is 5 or more higher. More preferably, it is 6 or more, even more preferably 7 or more, and particularly preferably 7.5 or more. Since the fluidity of the carbon-coated metal particles is highly dependent on the original raw material particles, it is important that the relative value (relative to the core particle) is good in order to express the effect of the carbon layer as well as the absolute value as described above.
[0025] The carbon-coated metal particles of the present invention preferably have an oxidation onset temperature that is 5°C or higher than that of the raw metal particles or particles obtained by removing the carbon coating layer from the carbon-coated metal particles. In other words, the carbon coating layer has the effect of suppressing oxidation of the metal. The oxidation temperature is more preferably 10°C or higher. The oxidation temperature can be evaluated by comparing the temperature at which the weight of the particles increases by 5% using thermogravimetric analysis (e.g., TG-DSC) in an air atmosphere (when a metal is oxidized, its weight increases due to the amount of oxygen).
[0026] The carbon-coated metal particles of the present invention preferably have higher water resistance and / or acid resistance than the raw metal particles or particles obtained by removing the carbon coating layer from the carbon-coated metal particles. That is, the effect of the carbon coating layer can improve the water resistance and / or acid resistance of the metal. The water resistance and / or acid resistance can be evaluated by stirring the particles in water (warm water) or dilute hydrochloric acid (e.g., pH 2) and comparing the amount of gas (e.g., hydrogen) generated.
[0027] [Metal particles] The metal particles, which are the raw material of the carbon-coated metal particles of the present invention, are preferably metal particles consisting of one component, or alloy particles containing one or more metal components and one or more elements. They may also be a mixture of two or more metal or alloy particles. The metal particles are preferably Mg, Al, Ti, Cr, Mn, Fe, Co, Ni, Cu, Zn, Y, Zr, Nb, Mo, Ru, Rh, Pd, Ag, In, Sn, La, W, Ir, Pt, Au, Pb, or Bi. As the alloy particles, stainless steel (containing Fe and Cr, and containing one or more elements such as C, Si, Al, Mn, Ni, Co, Mo, V, W), nickel alloy (containing Ni, and containing one or more elements such as B, C, Si, Al, Cu, Cr, Fe, Mo, Nb, W), aluminum alloy (containing Al, and containing one or more elements such as Cu, Mn, Ti, Si, Mg, Zn, Ni), magnesium alloy (containing Mg, and containing one or more elements such as Al, Zn), cobalt alloy (containing Co, and containing one or more elements such as C, Cr, Al, Ni, Mo, W, Y), titanium alloy (containing Ti, and containing one or more elements such as Al, Cr, V, Sn, Zr, Mo, Nb). The above elements include nonmetals, and for example, B, C, Si, etc. are preferable.
[0028] The metal particles that are the raw material for the carbon-coated metal particles of the present invention may have a layer of different components on the surface of the metal particles (e.g., a core-shell structure). Among them, it is preferable that the shell layer is a metal component. This allows the metal layer (or, in some cases, a metal oxide layer such as a passive layer) to be exposed on the surface, making it possible to coat the metal particles with carbon satisfactorily.
[0029] The metal particles that are the raw material for the carbon-coated metal particles of the present invention are preferably metal particles that form a passive state, which allows for stronger interaction with the carbon coating layer.
[0030] The shape of the metal particles that are the raw material for the carbon-coated metal particles of the present invention is not particularly limited, but from the viewpoint of flowability, they are preferably spherical or rounded, with spherical being particularly preferred.
[0031] The metal particles, which are the raw material of the carbon-coated metal particles of the present invention, preferably have a high melting point of 600° C. or higher. The high melting point makes it possible to carry out the heating and sintering step described below well. The melting point is more preferably 700° C. or higher, and even more preferably 800° C. or higher.
[0032] The method for producing the metal particles, which are the raw material for the carbon-coated metal particles of the present invention, is not limited, but from the viewpoint of fluidity, those produced by an atomization method are preferred. Among these, water atomization and gas atomization are particularly preferred. With the carbon-coated metal particles of the present invention, even metal particles produced by a water atomization method or a gas atomization method can be given better fluidity and high quality due to the effect of the carbon coating layer.
[0033] [Carbon-coated stainless steel particles] The carbon-coated metal particles of the present invention are preferably carbon-coated stainless steel particles. The carbon-coated stainless steel particles of the present invention are preferably observed to undergo reduction of chromium oxide by carbon (associated weight loss) when heated (for example, at 10°C / min up to 1500°C) in an argon atmosphere in a thermogravimetric analysis (for example, TG-DSC). The reduction of chromium oxide during heating makes it possible to remove impurities such as carbon and oxides.
[0034] The carbon-coated metal particles of the present invention exhibit a peak attributable to chromium oxide (560 cm -1 The presence of chromium oxide means that a passivity characteristic of metals is present. This allows the metal to function. More preferably, the metal has a peak (around 680 cm) derived from iron chromium oxide or manganese chromium oxide. -1 It is also preferable to have a
[0035] [Stainless steel particles] The stainless steel particles, which are the raw material (core particles) of the carbon-coated stainless steel particles of the present invention, are alloys containing iron and chromium, and are preferably austenitic (SUS304, etc.), ferritic (SUS430, etc.), austenitic-ferritic (two-phase) (SUS329J1, etc.), or martensitic (SUS410, etc.) The components of the stainless steel particles may include, in addition to iron and chromium, carbon, cobalt, nickel, molybdenum, manganese, copper, silicon, phosphorus, and sulfur.
[0036] The method for producing the stainless steel particles is not limited, but from the viewpoint of fluidity, those produced by an atomization method are preferred. Among these, water atomization and gas atomization are particularly preferred. In the carbon-coated stainless steel particles of the present invention, even stainless steel particles produced by a water atomization method or a gas atomization method can be given better fluidity and high quality due to the effect of the carbon coating layer.
[0037] The stainless steel particles of the present invention preferably include particles having a particle size of 1 μm or more and 100 μm or less, as measured by observation with an optical microscope or a scanning electron microscope.
[0038] The stainless steel particles of the present invention preferably have a volume average particle size D50 of 10 μm or more and 100 μm or less.
[0039] [Carbon coating layer] The carbon coating layer of the carbon-coated metal particles of the present invention preferably has an average thickness of 10 nm or less. This can be evaluated by observing 10 randomly selected particles with a transmission electron microscope. It is more preferably 7 nm or less, and most preferably 5 nm or less.
[0040] The carbon coating layer of the carbon-coated metal particles of the present invention has a G band (1580 cm due to the benzene hexagonal mesh structure) in Raman spectroscopy. -1 In addition, the D band (at 1350 cm due to defects and functional groups) -1It is preferable that the graphene has a peak in the vicinity of the G' band (at 2700 cm -1 It is preferable that the carbon coating layer has a peak in the vicinity of the peak. By having these peaks, it can be characterized as having a skeleton as a carbon material, and it can be said to be a good carbon coating layer.
[0041] The carbon coating layer of the carbon-coated metal particle of the present invention preferably has a coverage rate of 80% or more relative to the particle. This results in a high-quality carbon coating layer. The coverage rate can be evaluated in Raman spectroscopy by analyzing 100 random points on the particle and measuring the proportion at which the G-band peak is observed. The coverage rate is more preferably 90% or more, and most preferably 95% or more.
[0042] [Soluble carbon material] The soluble carbon material of the present invention is soluble in a solvent. General carbon materials (graphite, activated carbon, carbon black, graphene, carbon nanotubes, etc.) are insoluble in a solvent. Some of them are dispersible, but essentially, soluble in a solvent means that it dissolves in the solvent, and for example, when it is passed through a membrane filter (for example, 0.1 or 0.45 μm pore size), it passes through. On the other hand, general carbon materials cannot pass through. That is, whether or not it is soluble is determined by mixing the carbon material to a solvent so that it is 0.01% by mass, performing ultrasonic treatment for 1 hour, and passing the resulting liquid through a GL Chromatodisc (model 13P, pore size 0.45 μm) manufactured by GL Sciences Inc. If the carbon material passes through the filter paper, it is said to be soluble in the solvent. If the carbon material to be coated is soluble in the solvent, it is possible to coat the particles in a state where they are sufficiently dispersed in the liquid phase, and since the carbon component is dissolved (present in angstrom to nano size), it is possible to coat the particles thinly and uniformly. In addition, the solubility of the carbon facilitates the removal of excess carbon components.
[0043] The solvent in which the soluble carbon material of the present invention is soluble is not particularly limited, and examples thereof include nitrogen-containing solvents such as N,N-dimethylformamide and N-methylpyrrolidone, ketone solvents such as acetone, ester solvents such as ethyl acetate, alcohol solvents such as ethanol and 2-propanol, halogen-based solvents such as chloroform, and water. The solvent may be one type or a mixed solvent of two or more types. Among these, it is particularly preferable that the soluble carbon material is soluble in N,N-dimethylformamide.
[0044] In Raman spectroscopy, the soluble carbon material of the present invention preferably has a peak in the G band, more preferably a peak in the D band, and more preferably a peak in the G′ band (2700 cm owing to the benzene hexagonal mesh structure). -1 It is preferable that the carbon material has a peak in the vicinity of the peak. By having these peaks, the carbon material can be characterized as having a skeleton, and good carbon coating can be achieved.
[0045] The soluble carbon material of the present invention may be, for example, a precursor compound such as polyhydric phenols (compounds having two or more phenolic hydroxyl groups in the structure) such as phloroglucinol and hexahydroxytriphenylene, or polyphenols such as catechin, which preferably release water molecules during carbonization and are polymerized and carbonized. The soluble carbon material can be obtained by calcining the precursor compound at a low temperature of 300°C or less. The main calcination temperature is preferably 200°C or more and 300°C or less. The atmosphere during the main calcination is not particularly limited, and the material can be suitably used in any of air, vacuum, and inert gas atmosphere.
[0046] The soluble carbon material and its precursor of the present invention preferably do not contain halogen, nitrogen, or sulfur elements in order to suppress adverse effects on metal particles. These impurity elements can be evaluated by XPS analysis. The content of each of the halogen, nitrogen, and sulfur elements is 1000 ppm or less, particularly preferably 500 ppm or less, and most preferably 100 ppm or less.
[0047] [Method of manufacturing carbon-coated metal particles] In the method for producing carbon-coated metal particles of the present invention, the metal particles are preferably coated by contacting the soluble carbon material with the metal particles in a solvent (contact step). The contact can be, for example, (1) mixing the soluble carbon material with the metal particles in a solvent. At this time, the soluble carbon material may be added to the solvent first, the metal particles may be added first, or they may be added simultaneously. The contact can also be, for example, (2) baking the metal particles and the soluble carbon material raw material in a mixed state, generating the soluble carbon material in the mixed state, and then adding the solvent. In both (1) and (2), the soluble carbon material can uniformly cover the metal surface. The solvent is not particularly limited, and may be a solvent in which the soluble carbon material is soluble or insoluble, or a solvent in which it can only be dispersed, but from the viewpoint of being able to maximize the effects of the present invention, the above-mentioned solvent in which the soluble carbon material is soluble is preferable.
[0048] In the method for producing carbon-coated metal particles of the present invention, the contact may be performed at room temperature, or may be heated in a solvent. The heating temperature is not particularly limited, but is preferably 200° C. or lower. The boiling point of the selected solvent can be used as the maximum temperature.
[0049] In the method for producing carbon-coated metal particles of the present invention, a dispersion treatment may be used in the contact step in the solvent in order to improve the dispersibility of the metal particles. Examples of the dispersion treatment include shear treatment using a mixer or homogenizer, and ultrasonic treatment.
[0050] In the method for producing carbon-coated metal particles of the present invention, it is also preferable to add a solvent after the contact and remove the solution in which the soluble carbon material has been dissolved. Alternatively, it is also preferable to remove the solution in which the soluble carbon material already exists. In other words, it is also preferable to dissolve and wash the soluble carbon material that is not involved in the carbon coating with a solvent. It is also preferable to purify the material by repeatedly removing excess solution and adding a solvent. The purification step can be performed by centrifugation, filtration, decantation, etc. The solvent in the purification step may be the same as the solvent used in the contact step, or it may be a different solvent.
[0051] In addition, by adjusting the amounts of the soluble carbon material and the metal particles to be contacted in the purification step, it is possible to achieve uniform coating without purification, i.e., the purification step may or may not be performed.
[0052] In the method for producing carbon-coated metal particles of the present invention, it is also preferable to heat and sinter the metal particles after contacting the soluble carbon material with the metal particles (heating and sintering step). By heating and sintering, the bond between the metal particles and the carbon coating layer can be strengthened, and the carbonization of the carbon coating layer also progresses. The temperature of the heating and sintering step is preferably 300°C to 1000°C, more preferably 500°C to 900°C, and most preferably 600°C to 800°C. At this temperature, carbonization can proceed smoothly and the bond can be strengthened. The atmosphere for the heating and sintering step is preferably a vacuum or an inert gas atmosphere from the viewpoint of avoiding combustion of the carbon coating layer. EXAMPLES
[0053] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. In addition, unless otherwise specified, "parts" means "parts by mass" and "%" means "% by mass".
[0054] [Raman spectroscopy] The microscopic laser Raman spectroscopy was carried out using the following equipment and conditions. JASCO NRS-3100, excitation wavelength 532 nm, number of integrations 128
[0055] [X-ray photoelectron spectroscopy (XPS) measurement] The XPS analysis was carried out using the following equipment and conditions. Shimadzu Kratos AXIS-NOVA X-ray source, output AlKα―100W, pass energy 40eV, neutralization gun ON Generally, the peak due to carbon-oxygen bonds in O1sXPS appears around 532-533 eV. For each metal particle, fitting is possible using previous literature. Generally, the energy peaks below that are due to metal oxides.
[0056] [TG-DSC measurement] The differential scanning calorimetry-thermogravimetry simultaneous measurement (TG-DSC) was performed using the following equipment and conditions. Netsch, STA 449 F5 Jupiter, Using an alumina pan, under argon and air atmosphere, Analysis from 50 to 1500°C or 50 to 700°C at a heating rate of 10K / min.
[0057] [Carr Liquidity Index Rating] Carr's fluidity index evaluation was carried out using the following apparatus and conditions. Evaluation of powder flowability using a powder property evaluation device (Hosokawa Micron, PT-X) (Based on analysis of angle of repose, spatula angle (average angle before and after impact), compressibility, and uniformity)
[0058] [Examples 1 to 3] Phloroglucinol was baked at 300°C for 1 hour in an air atmosphere using a tube furnace to synthesize a soluble carbon material. The soluble carbon material was confirmed to have G, D, and G' bands by Raman spectroscopy. It was also soluble in N,N-dimethylformamide. No elements other than C and O were identified by XPS analysis (100 ppm or less, excluding H element which cannot be analyzed). Furthermore, 100 parts by mass of stainless steel (SUS316L, SUS430, SUS410L, each with an average particle size of 30 μm) particles (synthesized by gas atomization method) were suspended in N,N-dimethylformamide, and the soluble carbon material (1 part by mass) dissolved in N,N-dimethylformamide was added thereto and mixed. After stirring for 30 minutes, the mixture was filtered and washed with N,N-dimethylformamide to obtain carbon-coated stainless steel particles (before baking). The obtained carbon-coated stainless steel particles (before calcination) were heated and calcined at 800°C for 2 hours in a nitrogen atmosphere to obtain carbon-coated stainless steel particles. Raman spectroscopy confirmed that all three types of carbon-coated stainless steel particles had G and D bands and peaks due to chromium oxide. Optical microscope observation confirmed that the particles contained particles with particle sizes of 1 μm or more and 100 μm or less. TG-DSC analysis also confirmed a weight loss due to the reduction of chromium oxide. Raman spectroscopy analysis of the molten solidified material obtained by TG-DSC also revealed that the G and D bands had disappeared. All three types of carbon-coated stainless steel particles obtained had a carbon content of 0.3% or less.
[0059] [Comparative Examples 1 to 3] Stainless steel particles (SUS316L, SUS430, SUS410L) were used as they were. Raman spectroscopy did not confirm the G and D bands for all three types of stainless steel particles. Furthermore, TG-DSC analysis did not confirm the reduction of chromium oxide.
[0060] [Comparative example A] For comparison with the solid-phase method, stainless steel (SUS316L) particles were mixed with graphite (particle size 25 μm) at 1%, and the mixture was stirred overnight in a ball mill using zirconia balls. Excess graphite was essential to coat the entire particle surface with carbon, and it was difficult to avoid particles consisting only of carbon (only graphite). The carbon content of these carbon-coated stainless steel particles was 1.0%. As the amount of coating increased, the oxidation resistance and acid resistance improved.
[0061] [Comparative example B] For comparison with the gas-phase method, stainless steel (SUS316L) particles were placed on a quartz boat and, using a tubular furnace, the particles were stirred appropriately with a quartz rod while flowing nitrogen, and a thermal CVD method was used to form a film for one hour while flowing an ethanol-nitrogen mixed gas (0.1% ethanol) at 900°C to obtain carbon-coated stainless steel particles. In order to coat the entire particle surface with carbon, it was inevitable that carbon would accumulate, and this area peeled off, leading to the production of particles consisting only of carbon. The carbon content of these carbon-coated stainless steel particles was 1.8%. As the amount of coating increased, the oxidation resistance and acid resistance improved.
[0062] [Comparative example C] For comparison with the liquid-phase method using graphene oxide, stainless steel (SUS316L) particles were mixed and dried in 2-propanol so that graphene oxide (Nishina Materials, 30 μm) was 1%. The obtained particles were reduced at 700°C in a nitrogen atmosphere to convert the graphene oxide into graphene, obtaining carbon-coated stainless steel particles. The carbon content of these carbon-coated stainless steel particles was 0.7%. When attempting to coat the particles with graphene oxide, it was difficult to avoid the generation of particles consisting only of carbon (only graphene oxide). As the amount of coating increased, the oxidation resistance and acid resistance improved.
[0063] [Examples 4 to 7] Carbon-coated alloy particles were produced in the same manner as in Example 1, using Ni-Cr-Mo alloy particles equivalent to Hastelloy as representative nickel alloy particles, Al-Mg-Si alloy particles equivalent to the A6000 series as representative aluminum alloy particles, Mg-Al-Zn alloy particles equivalent to the AZ series as representative magnesium alloy particles, and Ti-Al-V alloy particles equivalent to T15 as representative titanium alloy particles (each particle synthesized by gas atomization).
[0064] [Comparative Examples 4 to 7] The raw material particles were used as they were in Examples 4 to 7. G and D bands could not be confirmed by Raman spectroscopic analysis for all four types of raw material particles.
[0065] As an example, the analysis results for SUS316L are shown in Figure 1 as the Raman spectroscopic analysis results of the particles, in Figure 2 as the microscopic observation results, in Figure 3 as the TG-DSC analysis results, and in Figure 4 as the Raman spectroscopic analysis results of the melt-solidified material. (SUS316L is Comparative Example 1, and Carbon-coated SUS316L is Example 1.)
[0066] The fluidity evaluation results of the particles of Examples 1-7, Comparative Examples 1-7, and AC are summarized in Table 1. From the above results, the carbon coating of the present invention resulted in metal particles with high fluidity. Other parameters of the particles of Examples 1-7, Comparative Examples 1-7, and AC are summarized in Table 2. From the above results, the carbon coating of the present invention resulted in high-quality metal particles. In particular, in the existing carbon coating method, compared to gas atomized raw material particles that originally have high fluidity, the repose angle and spatula angle were improved, but the compressibility was very poor. This is thought to be due to the fact that the carbon coating is not uniform and particles consisting only of carbon are mixed in.
[0067] Table 1 shows parameters relating to the fluidity of the carbon-coated metal particles obtained in the examples and comparative examples.
[0068] [Table 1]
[0069] Table 2 shows the evaluation results of Raman spectrum analysis, XPS analysis, etc.
[0070] [Table 2]
[0071] In the table, if the G band / D band is observed, it is marked with a circle, and if not, it is marked with a cross. Particles consisting of only carbon, and the proportion of CO in O1sXPS are not evaluated for metal particles consisting of only metal particles (each comparative example). The oxidation temperature, water resistance, and acid resistance are compared between each example and the corresponding comparative example (of the same metal).
[0072] The carbon-coated metal particles of the present invention exhibit good fluidity and can be used as particles with excellent handling, transportability, and packing properties, and can be used in powder metallurgy, sintering, 3D printers, welding applications, and the like.
Claims
1. A carbon-coated metal particle characterized by having a G-band peak in a Raman spectrum obtained by Raman spectroscopy, and characterized by having a Carr fluidity index of 70 or more.
2. A carbon-coated metal particle characterized by having a G-band peak in a Raman spectrum obtained by Raman spectroscopic analysis, and characterized in that the number ratio of particles consisting only of carbon is 1% or less when the particles are observed with an electron microscope or an optical microscope.
3. The carbon-coated metal particles are characterized by having a G-band peak in a Raman spectrum obtained by Raman spectroscopy, and by the ratio of the total peak area derived from carbon-oxygen bonds to the total bond peak area being 10% or more when analyzed by O1s XPS.
4. 4. The method for producing carbon-coated metal particles according to claim 1, which comprises contacting a carbon material that is soluble in a solvent with carbon-coated metal particles.
5. The method for producing carbon-coated metal particles according to claim 4, characterized in that the contact is carried out in a solvent.
Citation Information
Patent Citations
Opening and closing device for hatch cover
JP1978087486A
Coated particle and formed body
JP2018184639A
Carbon-coated metal powder, powder material for additional production comprising the same, and method for producing additionally produced article
JP2018199862A
Three-dimensional molding alloy powder
JP2021085063A